Utilization of Fly And Rice Husk Ashes Waste in The Making of Lightweight Brick in Supporting Construction Materials in Banyuwangi - M. Shofi’ul Amin; Mirza Ghulam R.; Galang S; Rysmayang . (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
The high specific gravity of concrete, which ranges around 2400 kg/m³, will affect the loading of relatively large and heavy structures. This will affect the total weight of the building which can lead to wasteful dimension of foundations which tend to affect the structural behavior in high earthquake areas; the more the weight of the structure, the greater the effect of the earthquake for the building. One alternative material to reduce the weight of the building is lightweight building materials, such as light brick. This study aims to determine the characteristic properties of mortar which is the lightweight brick base material by using the proportion of fly ash and rice husk ash as a substitute for heavy cement with the addition of aluminium powder and when the duration of steam curing is 6 hours at 60oC. The results of the maximum mortar compressive strength occur in a mixture of PC90%: Psr100%: FA10%: AP0%, which is equal to 13.5 MPa. As for the mortar with added ingredients in the form of aluminium powder, the maximum compressive strength of the mixture of PC90%: Psr100%: FA10%: AP0.2%, which is equal to 5.1 MPa. The correlation between specific gravity and compressive strength of mortar can be seen from the low value of specific gravity and high value of compressive strength on the mortar occurring in a mixture of PC90%: Psr100%: PS10%: AP0% with a value of 1.6 kg / cm2 and 5.1 MPa.